THE FLAVONOID AND ALKALOID CONTENT OF CYCLOSORUS PARASITICUS (LINN.) FARWELL FERNS AT THE PLANTATION AREAS OF JEMBER REGENCY - Dwi Setyati; Hari Sulistiyowati; Monica Paulina Erizcy; Tri Ratnasari (Universitas Medan Area, 2020)
Cyclosorusparasiticus(Linn.) Farwell is one potential medicinal ferns. The plant contains secondary metabolites, such as flavonoids and alkaloids. This study aims to determine the flavonoid and alkanoidofCyclosorusparasiticus (Linn.) Farwell in three plantation areas of Jember Regency. Plant samples were collected from Mount Gumitir coffee plantations, Pine Garahan Village and rubber and cocoa plantations in Tancak in Jember. Samples of stems and leaves were dried at room temperature and then blended to obtain a powder. One gram of powder samples was macerated in 90 ml of methanol for 3x24 hours then was concentrated with an evaporator to obtain a crude extract. The crude extract was tested qualitatively for flavonoids and alkaloids by the Willstätter and Dragendorff methods followed by quantitatively tests with Spectrophotometric. The results showed thatboth flavonoids and alkaloids were found in stem and leavesof Cyclosorusparasiticus (Linn) Farwell growing at three research locations. The flavonoids and alkaloidsin content found in leaveswas higher than those in stem organs. The leaves of Cyclosorusparasiticus (Linn) Farwell in Gumitir contain the highest flavonoids and alkaloidscontentsthan those in Tancak.